Novel Acid Anthraquinone Dyes and Their Application on Various Fibres and Microbial Studies - PATEL, N.B.; PATEL, A.L. (Asian Journal of Chemistry, 2010)
Various anthraquinone acid dyes have been synthesized by condensation of bromamine acid with N-methylpiprazine. This condensed product was diazotized and coupled with various naphthalene based acid coupling components to get novel series of acid anthraquinone dyes. The dyeing performance on wool, silk and nylon fibres has been assessed. These dyes have been found to give a wide range of orange to violet shades on each fibre. All the dyes give good to very good light fastness on each fibre. The percentage dye-bath exhaustion on different fibres was good and acceptable. The dyed fibres showed moderate to very good fastness to light, washing and rubbing. All the synthesized dyes have been screened for their antimicrobial activity.